Association between vitamin D and uterine fibroids: a study protocol of an open-label, randomised controlled trial. Issue 11 (6th November 2020) - Sheng, Bo; Song, Yizuo; Liu, Yi; Jiang, Chenchen; Zhu, Xueqiong
Abstract : Introduction: Uterine fibroids are the most common pelvic benign tumour with no satisfactory long-term medical treatment. Recent studies have demonstrated that vitamin D significantly inhibited the growth of fibroids in vitro, vivo and a small-sample clinical trial. Therefore, the aim of this randomised clinical trial (RCT) is to evaluate whether supplementation with vitamin D could reduce the risk and inhibit the growth of uterine fibroids in reproductive stage women. Methods and analysis: The open-label, RCT comprises two parts, including parts I and II. In part I, 2230 vitamin D deficiency or vitamin D insufficiency patients without uterine fibroids will be randomly assigned to two groups: intervention group (according to the level of serum 25-hydroxyvitamin D3, receive 1600 or 800 IU/day of vitamin D3 for 2 years) and control group (followed up at the same time points). By using gynaecological ultrasound examinations, the incidence of uterine fibroids will be employed to measure the outcome in different groups. In part II, 360 uterine fibroids patients with vitamin D deficiency or vitamin D insufficiency will be randomly assigned to intervention group or control group. According to the level of serum 25-hydroxyvitamin D3, 180 patients will receive 1600 or 800 IU/day of vitamin D3 for 2 years. Control group will receive regular follow-up. The outcome measure will be conducted using gynaecological ultrasound examinations to detect the growth of uterine fibroids in each group. Ethics and dissemination: This study has been approved by the institutional review board of the Second Affiliated Hospital of Wenzhou Medical University (No. LCKY2018-35). Trial registration numbers: NCT03586947 and NCT03584529 .